2010
DOI: 10.21071/az.v60i232.3978
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutricional e características estruturais de gramíneas tropicais sob adubação nitrogenada

Abstract: O experimento foi conduzido na Fazenda Experimental da Unioeste, Marechal Cândido Rondon, PR, Brasil, com o objetivo de avaliar os efeitos de doses crescentes de N sobre características estruturais e composição química de três gramíneas forrageiras tropicais. O delineamento experimental utilizado foi o em blocos casualizados em es-quema fatorial 3 x 4, com três forrageiras tropicais (Panicum maximum cvs. tanzânia e mombaça, e Brachiaria sp. cv. mulato) e quatro doses de N (0; 40; 80 e 160 kg/ha) tendo como fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
5
0
4
Order By: Relevance
“…This response probably occurred because the nitrogen of the conventional urea was released faster, and with this the loss of nitrogen by volatilization was higher, reducing the efficiency of nitrogen use by the plant. Castagnara et al (2011), evaluating tropical grasses, also observed a decreasing linear effect of nitrogen fertilizer doses on L/S ratio. PDTC: population density of tiller per clump; LM/DM: live material/dead material ratio; TFB: total forage biomass; GLB: green leaf biomass; GSB: green stem biomass; MSE: mean standard error; *: significant at p < 0.05.…”
Section: Resultsmentioning
confidence: 84%
“…This response probably occurred because the nitrogen of the conventional urea was released faster, and with this the loss of nitrogen by volatilization was higher, reducing the efficiency of nitrogen use by the plant. Castagnara et al (2011), evaluating tropical grasses, also observed a decreasing linear effect of nitrogen fertilizer doses on L/S ratio. PDTC: population density of tiller per clump; LM/DM: live material/dead material ratio; TFB: total forage biomass; GLB: green leaf biomass; GSB: green stem biomass; MSE: mean standard error; *: significant at p < 0.05.…”
Section: Resultsmentioning
confidence: 84%
“…This variable is important because it allows for the evaluation of the increase in the proportion of leaves, which is a valuable variable for grazing livestock, and proportions of stems, both of which contribute to forage growth. Castagnara et al (2011) stated that the leaf:stem ratio is essential for animal nutrition, because it is associated with the ease of forage prehension. The decrease in leaf:stem ratio found in RP 28days caused by the increase in N level may be related to rapid plant development because of nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…No aspecto técnico, muitos deles obtiveram maus resultados, especialmente econômicos. Alguns estudos atribuem o mau resultado ao não ajuste no manejo do pastejo na medida de aplicação da adubação ou aplicação de técnicas e estratégias de adubação (CASTAGNARA et al, 2011;MARTUSCELLO et al, 2006;MESQUITA;NERES, 2008;PACIULLO;GOMIDE;RIBEIRO, 1998)…”
unclassified
“…demonstraram que plantas adubadas com N (independente do método de pastejo adotado) atingem um número máximo de folhas por perfilho de forma precoce, o que resulta na diminuição na duração de vida das folhas, resultando em decréscimos na eficiência de utilização e produtividade do sistema de pastagem. Em contrapartida, para uma dada condição de ambiente favorável (regime pluviométrico e térmico adequados) o nitrogênio pode gerenciar o ritmo de crescimento das plantas forrageiras, aumentando a velocidade dos ciclos de renovação -folhas e perfilhos no pasto (ALEXANDRINO et al, 2004;CASTAGNARA et al, 2011;FRICKE;MCDONALD;MATTSON-DJOS, 1997)…”
unclassified
See 1 more Smart Citation